2018
DOI: 10.3892/etm.2018.6061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of respiratory infection viruses in hospitalized children from Naples province in Southern Italy

Abstract: Most acute respiratory infections (ARIs) in children are due to viral etiology, and represent an important cause of mortality and morbidity in children <5 years old in developing countries. The pathogens that cause ARIs vary geographically and by season, and viruses serve a major role. In the present study, the distribution of the seven respiratory viruses that are more prevalent in Southern European countries were retrospectively analyzed in a Southern Italy Hospital, that centralizes pediatric diseases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
(34 reference statements)
4
15
0
Order By: Relevance
“…Calvo [ 17 ] reported a prevalence of ADV infection in November and December, though according to Kim [ 14 ], ADV did not show significant seasonality. Botti [ 18 ] indicated that ADV is mainly prevalent in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Calvo [ 17 ] reported a prevalence of ADV infection in November and December, though according to Kim [ 14 ], ADV did not show significant seasonality. Botti [ 18 ] indicated that ADV is mainly prevalent in summer.…”
Section: Discussionmentioning
confidence: 99%
“…al reported a high prevalence of rhinovirus, followed by RSV, parainfluenza virus, and less commonly influenza virus, metapneumovirus and coronavirus [ 37 ]. Another retrospective study published recently from Italy also identified rhinovirus as the most common virus, followed by adenovirus, RSV and parainfluenza whereas influenza virus and metapneumovirus were less common [ 38 ]. The differences in distribution may be attributed to the different viral detection kits that were used: the PneumoVir multiplex PCR, the FilmArray Respiratory Panel, and PureLink Viral RNA/DNA mini Kit respectively in the studies and to differences in inclusion criteria, seasonal variation, and population.…”
Section: Discussionmentioning
confidence: 99%
“…Calvo [17] reported a prevalence of ADV infection in November and December, though according to Kim [14] , ADV did not show signi cant seasonality. Botti [18] indicated that ADV is mainly prevalent in summer.…”
Section: Discussionmentioning
confidence: 99%